2020
DOI: 10.1111/and.13897
|View full text |Cite
|
Sign up to set email alerts
|

The function of long noncoding RNA HOTAIRM1 in the progression of prostate cancer cells

Abstract: Increasing life expectancy imposes big challenges to the global health of the male population, because some disorders, such as tumours, tend to progress with age (Bell et al., 2015). Among them, prostate cancer (PCa) is a leading cause of cancer-associated mortality among men, specifically in Western countries; the lowest rates of this cancer are seen in Africa and Asia. PCa has the highest heritability, accounting for almost 10% of all new male tumours. More than 650,000 men worldwide are diagnosed with PCa a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…For example, lncRNAs such as TUG1, SOX2-OT, LINC04080, LINC00115, LINC00689, NORAD, SNHG1, and LEF1-AS1 activate the Wnt signaling pathway and promote tumor growth and metastasis by regulating other ncRNAs or proteins ( Wang et al, 2019 ; Li et al, 2020a ; Chen et al, 2020 ; Meng et al, 2020 ; Song et al, 2020 ; Zhang and Li, 2020 ; Peng et al, 2021 ). Conversely, lncRNAs such as lncRNA625 and HOTAIRM1 inhibit the Wnt signaling pathway to suppress cancer, promote cell apoptosis, and inhibit cell proliferation in PCa ( Li et al, 2017 ; Wang et al, 2021 ). Investigation of the role of lncRNA625 in cancers has revealed that it promotes tumor development in esophageal carcinoma; however, it exerts a significant tumor-suppressive effect on PCa, suggesting that lncRNA625 could potentially serve as a therapeutic target for PCa ( Li et al, 2017 ; Guo-Wei et al, 2019 ).…”
Section: Type and Role Of Wnt Signaling Pathway-related Ncrnas In Pca...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, lncRNAs such as TUG1, SOX2-OT, LINC04080, LINC00115, LINC00689, NORAD, SNHG1, and LEF1-AS1 activate the Wnt signaling pathway and promote tumor growth and metastasis by regulating other ncRNAs or proteins ( Wang et al, 2019 ; Li et al, 2020a ; Chen et al, 2020 ; Meng et al, 2020 ; Song et al, 2020 ; Zhang and Li, 2020 ; Peng et al, 2021 ). Conversely, lncRNAs such as lncRNA625 and HOTAIRM1 inhibit the Wnt signaling pathway to suppress cancer, promote cell apoptosis, and inhibit cell proliferation in PCa ( Li et al, 2017 ; Wang et al, 2021 ). Investigation of the role of lncRNA625 in cancers has revealed that it promotes tumor development in esophageal carcinoma; however, it exerts a significant tumor-suppressive effect on PCa, suggesting that lncRNA625 could potentially serve as a therapeutic target for PCa ( Li et al, 2017 ; Guo-Wei et al, 2019 ).…”
Section: Type and Role Of Wnt Signaling Pathway-related Ncrnas In Pca...mentioning
confidence: 99%
“…In addition, the lncRNA HOTAIRM1 is highly expressed in mature bone marrow cells ( Zhang et al, 2014 ). Silencing HOTAIRM1 in PC3 cells promotes PCa cell apoptosis by downregulating the Wnt/β-catenin signaling pathway; however, the exact mechanism remains unknown ( Wang et al, 2021 ).…”
Section: Molecular Mechanisms and Functions Of Wnt Signaling Pathway-...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the mechanisms associated with ncRNAs in PCa. Through the integration of gene chip technology, second-generation sequencing, and data mining, multiple ncRNAs related to the occurrence and progression of PCa have been identified, including microRNA-4429, microRNA-596, microRNA-301a-3p, microRNA-3648, miR-29a-3p, miR-212-5p, miR-30a-5p, miR-324-3p, miR-452-5p, circPHF16, circITCH, lncRNA SNHG7, lncRNA LEF1-AS1, lncRNA HOTAIRM1, and LINC00115, among others [ 111 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. It was found that these ncRNAs regulate biological processes, such as cell proliferation, invasion, metastasis, and epigenetics, and play an essential part in PCa development.…”
Section: The Roles and Mechanisms Of Ncrnas Involved In The Wnt/β-cat...mentioning
confidence: 99%
“…HOXA transcript antisense RNA myeloid-specific 1 ( HOTAIRM1 ) is a lncRNA that was first reported in 2009. To date, it has been shown to be related to many kinds of human diseases, such as prostate cancer [ 21 ], anaplastic thyroid cancer [ 22 ], and acute myeloid leukaemia cells [ 23 ]. In glioma, studies have shown that HOTAIRM1 can maintain the tumourigenesis of GSCs and promote the proliferation, migration, and invasion of glioma cells [ 24 26 ]; however, its role in tMSCs in the glioma environment has never been studied.…”
Section: Introductionmentioning
confidence: 99%